2012
DOI: 10.2134/jeq2011.0313
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Concentrations of Fluoroquinolones and of Ciprofloxacin-resistant Enterobacteriaceae in Chicken Feces and Manure Stored in a Heap

Abstract: This study evaluated the impact of storing chicken manure on the degradation of enrofloxacin (ENR) and ciprofloxacin (CIP), and on the survival of CIP-resistant Enterobacteriaceae. At 24 d of age, half of 8900 chickens received ENR for 5 d. After the animals departed, their manure was stored in two heaps for 63 d. Enterobacteriaceae were cultured on media containing 0 to 32 mg L⁻¹ of CIP. A total of 320 isolates were fingerprinted using enterobacterial repetitive intergenic consensus-polymerase chain reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
(59 reference statements)
2
14
0
Order By: Relevance
“…Recognizing the importance of antibiotic‐resistant bacteria (ARB) and ARGs in livestock fecal material and applied manures, Pruden et al (2013) recently outlined specific management options for reducing the release of antibiotics and ARGs to the environment. Cited studies have shown the benefits of composting, stockpiling, and manure digestion on reduction of ARB and ARGs in manures (Nicholson et al, 2005; Moraru et al, 2012; Pei et al, 2007; Pruden et al, 2013). However, limitations in resources (e.g., time, space, and money) often necessitate application of manures without prior treatment (Nicholson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing the importance of antibiotic‐resistant bacteria (ARB) and ARGs in livestock fecal material and applied manures, Pruden et al (2013) recently outlined specific management options for reducing the release of antibiotics and ARGs to the environment. Cited studies have shown the benefits of composting, stockpiling, and manure digestion on reduction of ARB and ARGs in manures (Nicholson et al, 2005; Moraru et al, 2012; Pei et al, 2007; Pruden et al, 2013). However, limitations in resources (e.g., time, space, and money) often necessitate application of manures without prior treatment (Nicholson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…() and Moraru et al . (). However, only the main metabolites EF and CF were analyzed in a limited time period, without continuous/daily analysis of the excreta.…”
Section: Introductionmentioning
confidence: 97%
“…In a study performed by Moraru et al . (), chickens were treated with EF 10% oral solution for 5 days (10 mg/kg bw).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and has a more complicated topology structure than EFX and NFX. In a previous study, Moraru et al (2012) reported that FQs pollutants in the research area derived entirely from inputs of chicken manure, which was therefore regarded as the sole input resource. Whenever a single type of manure is used in vegetable planting, FQs concentrations would certainly increase with the application of more manure.…”
Section: Discussion Fqs Pollution and Contributory Factorsmentioning
confidence: 99%